The GWP-Chart: an environmental tool for guiding urban planning processes. Application to concrete sidewalks - Arena, Pablo (My University, 2011)
The systematized study of urban morphology has led to the development of integrated tools based on the knowledge of the relation between physical density and urban form. These tools do help planners and decision makers; however, environmental data is rarely included in them. This paper presents the GWP-Chart, a method that combines urban planning tools with environmental data, obtained through the use of the life cycle assessment (LCA) results. In order to explain its use, three urban fabrics have been selected. According to their morphology and their ground space index (GSI) and public space ratio (PSR) values, the contribution of the sidewalk subsystem to the global impact per square meter of urban development can be quantified and communicated. The GWP-Chart is applicable to all types of urban fabrics and scales (street or square, island, fabric or district), as well as adaptable to any urban infrastructure or subsystem and can be extended to other environmental impacts. Its advantages lie in its accurateness, adaptability and ease of interpretation.
Keywords: Sustainable city, Carbon footprint, Mitigation, Concrete, Greenhouse gas (GHG) emissions